Annual Report on The Development of PPP in China
XI, 257 p. 51 illus., 37 illus. in color.
Keywords: This book gathers invited top experts on Public-Private partnership (PPP) in China, from both theoretical and practical fields, to present the most comprehensive analyses of PPP’s practice in China up to 2017. This timely book offers researchers and practitioners a thorough understanding of the PPP’s development in China, including its definition, its modes, its features as well as its many kinds of applications into different industries including medical care, environmental protection, education, public works, park development, etc. It addresses diverse themes in PPP analyses such as quantitative analyses and qualitative analyses; data statistics and case study, theoretical framework modeling and field study verification. The book is an overview of the Chinese PPP development through 2017.